Produção científica sobre as temáticas afro-brasileira e indígena nos Programas de Pós-graduação em Ciência da Informação no Brasil - Silva, Francisco Sávio da (2020)
This research was born from the perception about the importance of discussing ethnic-racial issues in the scope of Information Science, since in recent years we have contemplated, in numerous scientific fields, frequent questions that claim the insertion of themes related to peoples and social segments excluded historically. It seeks, then, to break with several oppressive paradigms aiming at the social universalization of the processes of organization, access and use of information, which contributes to the struggle for the rights of peoples long invisible and excluded from goods, not only economic, but also of means access to information and knowledge. The general objective of the research is to understand the dynamics of scientific production that addresses Afro-Brazilian and indigenous themes in 12 Information Science Graduate Programs in Brazil, covering the period between 2000 and 2018. These programs are conceived as local that disseminate information to diverse audiences from configurations of the social, cultural and political order, therefore, the phenomenon is linked to the Information Regime. Methodologically, the research is characterized as bibliographic, descriptive and exploratory, with a quantitative-qualitative and documentary approach, using dissertations and theses as a research source, involving a bibliometric and scientometric study. As a result, in the period proposed for the study from 2000 to 2018, there were a total of 2,756 documents, of which 2,058 were dissertations and 698 theses. In relation to the documents selected to compose the corpus of the research, 56 were recovered, being 44 dissertations and 12 theses. As noted, the Afro-Brazilian and indigenous themes are still little explored, therefore, it is necessary an effort on the part of teachers, programs and students so that these peoples actually participate in the information society, and that they act in academic discussions. It is understood that these Programs are systems in which information and knowledge are managed by specific actors, involving conflicts and interests between social groups and discourses, using information actions, linked to devices and giving rise to the artifacts of information.